2009
DOI: 10.1016/j.dld.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser endomicroscopy for the detection of mucosal changes in ileal pouch after restorative proctocolectomy

Abstract: BACKGROUND AND AIMSConfocal laser endomicroscopy is a novel technique to analyze living cells during ongoing endoscopy. Total proctocolectomy with ileal pouch anal anastomosis is the surgical procedure of choice for the management of ulcerative colitis and familial adenomatous polyposis. Pouchitis, a non-specific inflammation of the ileal reservoir, and dysplasia may affect the pouch after surgery. The aim of the present study was to assess the suitability of confocal laser endomicroscopy for the in-vivo diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Trovato et al (34) assessed ileal pouches using either confocal laser endomicroscopy in vivo or conventional histopathological analysis and found incidences of colonic metaplasia of 67.7% and 83.3%, respectively, as well as an incidence of villous atrophy of 83.3% using both techniques. In our study, both colonic metaplasia and villous atrophy were observed in 36.6% of patients, and no dysplasia was detected in either study.…”
Section: Discussionmentioning
confidence: 99%
“…Trovato et al (34) assessed ileal pouches using either confocal laser endomicroscopy in vivo or conventional histopathological analysis and found incidences of colonic metaplasia of 67.7% and 83.3%, respectively, as well as an incidence of villous atrophy of 83.3% using both techniques. In our study, both colonic metaplasia and villous atrophy were observed in 36.6% of patients, and no dysplasia was detected in either study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the host have suggested that there may be partial colonic metaplasia that occurs in the ileal pouch. 79 Villus shortening and crypt hyperplasia have been described, though histologic changes appear to be patchy and inconsistent. Some have argued that these changes may be secondary to inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In a case series of 18 patients, CLE was superior to white light endoscopy to identify patients with pouchitis [32]. With histopathology as the gold standard, CLE had an accuracy of 94.4% to define villous atrophy, inflammation, ulceration and colonic metaplasia in these patients, and was again used to target biopsies.…”
Section: Lower Gastrointestinal Tractmentioning
confidence: 99%